Predictors of recovery from severe acute malnutrition among 6–59 months children admitted to a hospital - Andargie, Assefa; Zewdie, Segenet (Frontiers in Public Health, 2024)
Background and aim Severe acute malnutrition is a threat to child survival as mortality rates in children with severe malnutrition are nine times higher. Globally, about 19 million children are severely malnourished. This study looked at children aged 6–59 months admitted to hospital to see how quickly they recovered from severe acute malnutrition as well as what factors predicted their recovery. Methods The study included 543 systematically chosen children with severe acute malnutrition who were admitted to the stabilization center of a hospital. Data from the patient registry were gathered using a retrospective follow-up study design. In order to find predictors of recovery, the Cox proportional hazard model was applied. Results From 543 children, 425 (78.27%) were recovered. The median survival time was 8 days. Having grade II edema, grade III edema, and pneumonia were negatively associated with recovery. Similarly, taking ceftriaxone, cloxacillin, and being on a nasogastric tube were associated with poor recovery. Conversely, better recovery rates were linked to exclusive breastfeeding and vitamin A supplementation. Conclusion Both the recovery rate and the median survival time fell within acceptable bounds. To boost the recovery rate, efforts are needed to lessen comorbidities.